PHOTOINHIBITION OF PSII IN EMILIANIA HUXLEYI (HAPTOPHYTA) UNDER HIGH LIGHT STRESS THE ROLES OF PHOTOACCLIMATION, PHOTOPROTECTION, AND PHOTOREPAIR(1) - Ragni, Maria (Journal of phycology, 2008)
© 2008 Phycological Society of America.